Membangun Kreatifitas Melalui Inovasi Pembelajaran Bagi Guru SMPN 1 Tegalampel Bondowoso di Era New Normal - Achmad Nuryadi; Mulyono; Shandy Pieter Pelamonia; I Gede Dharma U; Ramadhany Hananto P; Riga Mardika (Kanigara, 2022)
In preparation for offline learning, SMPN 1 Tegalampel Bondowoso needs many references on how to build creativity through learning innovation. Therefore, it is necessary to hold a workshop on Building creativity through learning innovation at SMPN 1 Tegalampel Bondowoso. The implementation of Community Service Program activities by the Physical Education Lecturer Team at PGRI University Adi Buana Surabaya went smoothly. The teachers of SMPN 1 Tegalampel Bondowoso were very enthusiastic about participating in every scheduled activity. In preparation for offline learning, SMPN 1 Tegalampel Bondowoso needs many references on how to build creativity through learning innovation. Starting from knowledge about the use of technology and the internet to access materials and conduct learning interactions, such as through websites (websites),